An Evaluation of the Causes and Effects of Soil Erosion in Kabale District. A case Study of Ikumba Sub-County. - Immaculate, Kebirungi (Kabale University, 2019)
Soil erosion refers to the removal of top layer of soil and subsequently transported and deposited in other low laying area. Transportation and deposition of soil in Uganda is because of three major agents that is water, wind and glaciers (on snow caped mountain of Rwenzori) although there other minor agents like high population. The study was to identify the causes and effects of soil erosion in Ikumba sub-county kabale district. The study was guided by three objectives; to identify the causes of soil erosion in Ikumba sub-county kabale district and to identify the possible the possible mechanisms of reducing the incurring soil erosion in Ikumba sub-county Kabale District. The study was carried out in three parishes of Nyaruhanga, Nyamabale and Nyakabungo parish from Ikumba sub-county Kabale Districts. The study targeted 93 people who were chosen by random sampling method. The research methods used included questionnaires, observation method and interview method. The study findings were tabulated and presented in frequency distribution tables and frequencies and later presented in figures that are pie charts and graphs. From the study, 32.3% of respondents reported that over cultivation is the major cause of soil erosion, this is followed by 21.5% of the respondents who attributed soil erosion to be caused by the nature of the soil, Bush burning was reported by 5.4% of the respondents also leads to soil erosion,10.7% of the respondents reported road construction as one of the factors leading to soil erosion, Deforestation was also reported to be among the causes of soil erosion at 10.7% and over grazing also at 10.7%. Among the effects of soil erosion in Ikumba sub county, 26.8% of the respondents revealed that soil erosion leads to loss of soil fertility, 32.3% of the respondents said that soil erosion leads to famine, 16.1% of respondents revealed that soil erosion results into destruction of human settlement and swamps as reported by 10.7% of the respondents and 6.4% of the respondents reported disease outbreak from eroded waste material.